Synthesis and in vivo anticancer evaluation of poly(organo)phosphazene-based metallodrug conjugates. Issue 36 (1st September 2017) - Hackl, Carmen M.; Schoenhacker-Alte, Beatrix; Klose, Matthias H. M.; Henke, Helena; Legina, Maria S.; Jakupec, Michael A.; Berger, Walter; Keppler, Bernhard K.; Brüggemann, Oliver; Teasdale, Ian; Heffeter, Petra; Kandioller, Wolfgang
Abstract : Macromolecular drug conjugates : Polymer conjugation reduces local side effects and tumor growth in vivo . Abstract : Within this work we aimed to improve the pharmacodynamics and toxicity profile of organoruthenium and -rhodium complexes which had previously been found to be highly potent in vitro but showed unselective activity in vivo . Different organometallic complexes were attached to a degradable poly(organo)phosphazene macromolecule, prepared via controlled polymerization techniques. The conjugation to hydrophilic polymers was designed to increase the aqueous solubility of the typically poorly soluble metal-based half-sandwich compounds with the aim of a controlled, pH-triggered release of the active metallodrug. The synthesized conjugates and their characteristics have been thoroughly studied by means of 31 P NMR and UV-Vis spectroscopy, ICP-MS analyses and SEC coupled to ICP-MS. In order to assess their potential as possible anticancer drug candidates, the complexes, as well as their respective macromolecular prodrug formulations were tested against three different cancer cell lines in cell culture. Subsequently, the anticancer activity and organ distribution of the poly(organo)phosphazene drug conjugates were explored in vivo in mice bearing CT-26 colon carcinoma. Our investigations revealed a beneficial influence of this macromolecular prodrug by a significant reduction of adverse effects compared to the free metallodrugs.